The Effect Of Position Promotion, Workload, And Work Environment On Employee Loyalty At PT. Sahassa Prima Niaga - Verren Julyanti; Pujiarti Pujiarti (Fakultas Bisnis, 2022)
This study aim to determine the effect of promotion, workload, and work environment on employee loyalty at PT. Sahassa Prima Niaga. Data was collected by distributing questionnaires with sample of 54 respondents and data processing carried out using the SPSS 25 program. From the results analysis obtained multiple linear equation Y = 0.300 + 0.330X1 + 0.297X2 + 0.450X3. From the analysis coefficient of determination obtained relationship between independent variable and dependent variable, determination value promotion is 22.2% and remaining 77.8% is influenced by other factors. The value of determining workload is 27.3% and remaining 72.7% is influenced by other factors. The work environment determination value is 32.8% and remaining 67.2% is influenced by other factors. Based on hypothesis test, it obtained that tcount for promotion is 1,719, tcount for workload is 2.413, and tcount for work environment is 2.276 with ttable of 2. So it can be conclud for the workload and work environment variables H0 is rejected and Ha is accepted, while for the promotion variable H0 is accepted and Ha is rejected. From the results of the F test, it is obtained that Fcount for promotion is 16.131 with significance level of 0.000, Fcount for workload is 10,945 with a significance level of 0.000, and Fcount for the work environment is 9.622 with a significance level of 0.000 where the value is greater than Ftable of 2.79. Thus, H0 is rejected and Ha is accepted because Fcount > Ftable and significant level is less than 0.05.